Strengthening Differentiated Instruction Through AI in Merdeka Curriculum Implementation at SDN Kelayan Timur 2 Banjarmasin: Pengabdian - Desi Hidayanti; Nonong Rahimah; Asy’ari (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This service aims to enhance teacher competence in differentiated instruction through Artificial Intelligence (AI) media. The implementation method included three stages: preparation (diagnostic observation, material development), implementation (3-day interactive training), and evaluation (unstructured interviews). Results indicated improvement in teachers' conceptual understanding and technical skills using AI platforms (ChatGPT, Gemini, BlackAI) for developing differentiated learning materials. Technical constraints were primarily experienced by senior teachers (>50 years) in interface navigation and prompt optimization. It is concluded that the multimodal training model effectively builds foundational competencies, with recommendations for sustained mentoring and development of a community of practice.